Componential Analysis in Covid-19 Related Lexicon - Wijayanti, Asri; Diani, Winasti Rahma (Universitas Muria Kudus, 2022)
Virus corona merupakan salah satu hal yang sangat sering dibicarakan satu tahun belakangan ini. Sejak Akhir Februari 2020, Indonesia memang sedang dikejutkan dengan datangnya satu virus yang menyerang beberapa orang dengan gejala mirip influenza. Dampak virus ini merugikan berbagai aspek, mulai dari kesehatan, perekonomian, pendidikan, politik, dan lainnya sehingga semua yang terdampak mengalami kondisi baru. Kondisi baru ini menimbulkan istilah-istilah baru bagi masyarakat. Teknik pengumpulan data yang dilakukan peneliti yaitu dengan metode simak bebas libat cakap. Analisis data menggunakan metode deskriptif dengan teknik analisis komponensial. Setelah dilakukan analisis terdapat kelompok leksikon covid-19, di antaranya (1) Leksikon Penyakit di Sekitar Covid-19, (2) Leksikon Kondisi Sosial Saat Covid-19, (3) Leksikon Wilayah Terdampak Covid-19, (4) Leksikon Insan yang Terdampak Covid-19, (5) Leksikon Proses Pengurangan Risiko Penularan Kasus Covid-19, (6) Leksikon Alat Pelindung Diri untuk Mencegah Covid-19, (7) Leksikon Jenis Sakit pada Penderita Covid-19, (8) Leksikon Perilaku untuk Mencegah Terinfenksi Covid-19, (9) Leksikon Jenis Tes untuk Mengonfirmasi Covid-19, dan (10) Leksikon Pengantaran Logistik untuk Penderita Covid-19.The corona virus is one of the things that is very often discussed in the past year. Since the end of February 2020, Indonesia has indeed been surprised by the arrival of a virus that attacks several people with influenza-like symptoms. The impact of this virus is detrimental to various aspects, ranging from health, economy, education, politics, and others so that all those affected experience new conditions. This new condition gave rise to new terms for the community. The data collection technique used by the researcher is the free-to-talk method. Data analysis used descriptive method with componential analysis technique. After the analysis was carried out, there were groups of Covid- 19 lexicon, including (1) Lexicon of Diseases Around Covid-19, (2) Lexicon of Social Conditions During Covid-19, (3) Lexicon of Areas Affected by Covid-19, (4) Lexicon of People who Affected by Covid-19, (5) Lexicon of the Process for Reducing the Risk of Transmission of Covid-19 Cases, (6) Lexicon of Personal Protective Equipment to Prevent Covid-19, (7) Lexicon of Types of Sickness in Patients with Covid-19, (8) Lexicon of Behavior to Prevent Infected with Covid-19, (9) Lexicon Types of Tests for Confirming Covid-19, and (10) Lexicon for Logistics Delivery for Patients with Covid-19.